JFQ volume 37 issue 4 Back matter (Journal of Financial and Quantitative Analysis, 2002)
In recent years, interest-rate modeling has developed rapidly in terms of both practice and theory. In this book, Riccardo Rebonato draws on his academic and professional experience to bring together and build on what theory and trading have to offer.